ENGLISH FOR ACADEMIC PURPOSES AND E-LEARNING: POINTS OF CONSISTENCY AND ISSUES - Dotti Campanatti, Ana Helena [UNESP]; Costa, Tamiris Destro [UNESP]; Kaneko-Marques, Sandra Mari [UNESP] (Unesp-faculdade Ciencias & Letras, 2020)
This article aims to consider and reflect upon the teacher's sense of plausibility, specifically for Academic Purposes, within the context of online classes. For this, we will examine some aspects of the concept of the teacher ' s sense of plausibility. as well as the concept of distance learning (DL) and, likewise, the definition of EAP's (English for Academic Purposes). Secondly, we will concentrate, specifically, on questions involving experience reports on Distance EAP courses. Finally, we will make considerations as to point out problems and possible outcomes to EAP approaches in Distance learning contexts.
Keywords: English language teaching; English for academic purposes; Distance learning